Упрости выражение 2(-5x-8)-3(x-4)-5(-8x+6) При x=-1

0 голосов
48 просмотров

Упрости выражение 2(-5x-8)-3(x-4)-5(-8x+6) При x=-1


Математика (22 баллов) | 48 просмотров
Дано ответов: 2
0 голосов
Правильный ответ
2(-5x-8)-3(x-4)-5(-8x+6) =

=-10x-16-3x+12+40x-30=

=(-10-3+40)x-46+12=

=27x-34====>>
x=-1====>>27*(-1)-34=-27-34=-61
(127k баллов)
0

Можешь найти его значение?

0

=27x-34====>>x=-1====>>27*(-1)-34=-27-34=-61

0 голосов

2(-5х-8)-3(х-4)-5(-8х+6)=-10х-16-3х+12+40х-30=27х-34
27х-34=27*(-1)-34=-27-34=-61.

(104 баллов)